Visual, olfactory, and nutritional stimuli of basil (Ocimum basilicum L.) in Tetragonisca angustula (Hymenoptera: Apidae) - Julitza M. Fuentes-Polo; Samuel D. Toncel-Pérez; Nataly de-la-Pava-Suarez (Revista U.D.C.A Actualidad & Divulgación Científica)
Bees are essential pollinators that use visual and olfactory stimuli to locate flowers in search of nutritional resources. Among flowering plants, aromatics are recognized for their medicinal properties, but little is known about the mechanisms involved in their interaction with floral visitors. This work aimed to determine how visual and olfactory stimuli of the basil flowers participate in attracting Tetragonisca angustula Illiger (1806), and how microorganisms associated with these flowers are involved. For this, the attraction of bees was evaluated according to the type of flower and the resource offered (nectar, pollen, or nectar + microorganisms), and the bees' attraction to the plant's volatiles was analyzed, evaluating plants with and without flowers and the attraction to the isolated microorganisms in them. During the first phase (visual), T. angustula bees preferred white panicle-shaped flowers and the nectar resource. In the second phase (olfactory), they chose flowering plants over non-flowering ones. When plants were offered together with isolated microorganisms, bees preferred the smell of the microorganisms over the smell of the plants with flowers. The attraction of T. angustula to basil plants is influenced by the structure and color of the flowers, as well as by the volatiles, and especially by the presence of microorganisms in them, despite primarily seeking nectar as a resource during the visit